Komunikasi Hiperpersonal dalam Presentasi Diri - Annisa Divia Zaliyanti; Ani Yuningsih (Bandung Conference Series: Public Relations, 2022)
Abstract. Self-presentation usually individuals will do impression management (impression management). The goal is that we can influence other people, so that we are liked by others, want to improve our position, maintain status and so on. Self-presentation identifies two components in impression management, first, impression-motivation, which describes how our motivation is to control other people who see us or to create certain impressions in other people's minds. In this study, researchers used qualitative research methods with a phenomenological approach. The theory used in this research is the theory of computer mediated communication (CMC), which is in accordance with the focus of the problem of social media activities in it. This study took the research subject of pontianak city youth with the object of research being activities on Instagram social media accounts with anonymous username. The results of this study, the intertwined communication process builds and responds to statements from communication opponents and creates relationships without distraction from the reality environment. Abstrak. Presentasi diri biasanya individu akan melakukan impression management (pengelolaan kesan). Tujuannya adalah supaya seorang individu dapat mempengaruhi orang lain, supaya kita disukai orang lain, ingin memperbaiki posisi, memelihara status dan sebagainya. Presentasi diri mengidentifikasikan dua komponen dalam pengelolaan kesan yaitu pertama, impression-motivation (motivasi pengelolaan), yang menggambarkan bagaimana motivasi yang kita miliki untuk mengendalikan orang lain yang melihat kita atau untuk menciptakan kesan tertentu dalam pikiran orang lain. Dalam penelitian ini, peneliti menggunakan metode penelitian kualitatif dengan pendekatan fenomenologi. Teori yang digunakan dalam penelitian ini yakni teori computer mediated communication (CMC), yang sesuai dengan fokus permasalahan kegiatan bermedia sos perbaiki ial didalamnya. Penelitian ini mengambil subjek penelitian mahasiswa kota pontianak dengan objek penelitiannya adalah aktivitas dalam akun media sosial Instagram dengan username anonym. Penelitian ini akan menghasilkan model proses komunikasi yang terjalin antara satu dengan yang lain dan menciptakan hubungan tanpa gangguan dari lingkungan realitas.